Wsparcie polityki europejskiej przez programy UE dla doskonalenia wielu kultur językowych na przykładzie projektów LINGUAPORTA, LOST IN... oraz ABC-LINGUATOUR - Pietrus-Rajman, Marianna Agnieszka (European Policy and EU Linguistic Diversity Programmes. LINGUAPORTA, LOST IN... and ABC-LINGUATOUR Projects, 2008)
The paper presents priorities of EU policy in regard to foreign language teaching, with discussion of premises, aims and input of the policy in improving communication in multicultural Europe as a result of LINGUAPORTA, LOST IN... and АВС-LINGUATOUR projects developed with support from EU programmes of Socrates / Lingua. Final products of these projects are presented: LINGUAPORTA Internet portal for students of Czech, German and Polish as a foreign language, and two interactive edutainment products: LOST IN... (for students of Czech, Danish, Dutch and Polish) and ABC-LINGUATOUR (Czech, German and Polish).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 149-157